Essential Aspects of Ergonomics in the Office Environment - Cevallos, Eddyn Fernando (Artes: Architecture, Technology and Sustainability, 2024)
Ergonomics in office environments is essential to prevent occupational hazards such as awkward postures and musculoskeletal disorders (MSDs), which affect the health and productivity of professionals. The literature review conducted in this article reflected how factors such as inadequate furniture, poor lighting, and excessive noise contribute to eye strain, stress, and injuries. The implementation of ergonomic measures, such as adjustable chairs, active breaks, and specialized devices, significantly reduces these problems, improving well-being and work efficiency. It is evident that the integration of ergonomic principles into architectural design, considering physical, cognitive, and environmental aspects, promotes safe and healthy environments. Furthermore, investment in ergonomics not only benefits workers' health but is also cost-effective by reducing costs associated with occupational diseases and increasing productivity, ensuring sustainable and efficient workspaces.
Keywords: Design; ergonomics; office environment; risk; awkward postures